The Impact of VAT Incentives and Macroeconomic Variables on Residential Property Sales Growth (A Case Study in Indonesia) - Deny Cahyadinanto Sanjoko; Wulan Oktabriyantina (Transpublika Publisher, 2026)
To support the recovery of Indonesia’s residential property market following the COVID-19 pandemic, the government implemented Government-Borne Value Added Tax (VAT DTP) incentives to stimulate housing demand. However, empirical evidence regarding the effectiveness of this policy under different macroeconomic conditions remains limited. This study examines the effects of residential property price growth (IHPR Growth), inflation, the BI policy rate, Government-Borne VAT incentives, and the COVID-19 pandemic on residential property sales growth in Indonesia. Quarterly time-series data from 2018Q1 to 2025Q4 were analyzed. Prior to estimation, Augmented Dickey-Fuller (ADF) and Phillips-Perron (PP) tests confirmed a mixture of I(0) and I(1) variables with no variable integrated of order two. Accordingly, the Autoregressive Distributed Lag (ARDL) model was employed to estimate both short-run and long-run relationships. The Bounds Test confirmed the existence of cointegration among the variables. The results show that IHPR Growth and Government-Borne VAT incentives have positive and significant effects on residential property sales growth, while inflation has a delayed negative effect. In contrast, the BI policy rate and the COVID-19 dummy are statistically insignificant. These findings highlight the positive role of Government-Borne VAT incentives in supporting residential property sales during the post-pandemic recovery. This study contributes by applying a dynamic ARDL framework and using IHPR Growth as a more appropriate explanatory variable for residential property sales growth.